DEGRADATION OF CHITOSAN BY γ-IRRADIATION OF CHITOSAN SWOLLEN IN HYDROGEN PEROXIDE SOLUTION - Du, Dang Xuan; Mai, Vo Quang; Duy, Nguyen Ngoc; Phu, Dang Van; Hien, Nguyen Quoc (Vietnam Journal of Science and Technology, 2014)
ABSTRACT Degradation of chitosan in swollen state with hydrogen peroxide solution (1–5% w/v) by γ-irradiation was investigated. Molecular weight (Mw) of irradiated chitosan samples was determined by gel permeation chromatography (GPC). Fourier transform infrared (FT–IR) spectra and X–ray diffraction (XRD) patterns were utilized to study the structure of degraded chitosan. Results showed that low Mw chitosan of ~30–45 kDa was efficiently prepared by γ–irradiation of chitosan (Mw0 ~91.7 kDa) swollen in hydrogen peroxide solutions at low dose less than 20 kGy. The main structure as well as the degree of deacetylation of degraded chitosan was almost unchanged. Furthermore, the radiation degradation yield (Gs) was remarkably enhanced with the presence of H2O2 as a sensitizer. Degradation of chitosan in swollen state with hydrogen peroxide solution by γ-irradiation is efficient for preparation of low Mw chitosan at low dose.